2017
DOI: 10.5539/gjhs.v9n7p168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gum Arabic as Dietary Supplement for Type II Diabetes in Jabir Abu Aliz Diabetic Center- (Khartoum State)

Abstract: BACKGROUND: Gum Arabic (Acacia Senegal) is a water-soluble dietary fiber considered to be safe by the United States Food and Drug Administration since the 1970s.Recent studies showed the therapeutic action of Gum Arabic.METHODS: It was Quasi-experimental study design. The objective of this study was to determine the effects of regular Gum Arabic ingestion as dietary supplement on accumulative blood glucose (HbA1c) and body mass index (BMI) among type II diabetes in Jabir Abu Aliz Diabetic Center in Khartoum. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…GA has an intrinsic glycaemic index is proximate zero snice it is not absorbed in small intestine (21). While Ibrahim et al at (2017) observed that in type II diabetic patients' ingestion of 60gm/day of GA produced no significant or appreciable effect on blood glucose concentration and body mass index (66) .…”
Section: Effect On Diabetesmentioning
confidence: 97%
“…GA has an intrinsic glycaemic index is proximate zero snice it is not absorbed in small intestine (21). While Ibrahim et al at (2017) observed that in type II diabetic patients' ingestion of 60gm/day of GA produced no significant or appreciable effect on blood glucose concentration and body mass index (66) .…”
Section: Effect On Diabetesmentioning
confidence: 97%
“…Recent studies explained the therapeutic effect of GA reporting that ingestion of 60 gm of GA on a daily basis for 90 days can induce minor decrease in the body mass index (BMI) of diabetics, and slight change in their glycated hemoglobin (HbA1c). This may be attributed to increased intake of carbohydrates in 60% of the respondents and disrespect of 32% of participants to the regular ingestion of GA dose prescribed [24].…”
Section: Role Of Ga In Reducing Fasting Plasma Glucose and Hba1cmentioning
confidence: 99%
“…Babiker et al [25] observed the beneficial effect of GA in glycemic control diabetic patients receiving 30 gm of gum for four months. GA has an intrinsic glycemic index of proximately zero since it is not absorbed in small intestine [26], while Ibrahim et al [24] published that in type II diabetic patients, ingestion of 60 gm/day of GA produced no significant or appreciable effect on blood glucose concentration and BMI.…”
Section: Role Of Ga In Reducing Fasting Plasma Glucose and Hba1cmentioning
confidence: 99%
“…The natural characteristics of GA associated with qualitative and quantitative indicators include moisture, ash content, volatile compounds, and inner energy, which exactly represents the world standards [8]. Recent studies have shown the therapeutic action of GA [9]. GA is used to treat many diseases as it improves the performance of the digestive system and improves the appetite [10].…”
Section: Introductionmentioning
confidence: 99%